Investigating Oral Cancer Awareness Among Medical and Dental Students: A Cross-Sectional Study in the South Canara Region of India - Shubham Agarwal; Nidhi Manaktala; Srikant Natarajan; Karen Boaz (The Scientific World Journal)
Oral cancer is responsible for increased mortality, especially in the Indian subcontinent. Habits like smoking and tobacco chewing are among the most common causes of oral cancer. Previously, these habits were seen mainly in the elderly; however, the trends have seemed to increase in the younger generation. Awareness regarding oral cancer is essential during the early years of a healthcare expert for effective diagnosis. This study aimed to investigate oral cancer awareness among medical and dental students. A cross-sectional study including 144 medical and 112 dental undergraduate students was designed. A validated 12-question questionnaire on oral cancer awareness was distributed to medical and dental undergraduate students. The collated data were analyzed statistically using tests of proportion. Dental students were more likely to examine oral mucosa routinely (χ2 = 9.585, p=0.002) and observe oral lesions like proliferative growth (χ2 = 71.763, p<0.001), while medical students reported higher incidences of poor oral hygiene (χ2 = 7.667, p=0.006) and tobacco usage (χ2 = 6.337, p=0.012). Both groups expressed a need for more education on oral cancer, with dental students showing a stronger preference (χ2 = 7.526, p=0.006). Referral to an oral surgeon was preferred among both groups. The dental students felt a lack of sufficient knowledge on oral cancer. It was observed that the knowledge and information regarding cancer-related symptoms was more among medical students. However, overall awareness regarding oral cancer was higher in dental students compared to medical students. It was concluded that medical students exhibited more knowledge about oral cancer causes, while dental students were more aware of its signs and symptoms. Educational interventions should be introduced early to reduce diagnostic delays and prevent cancer progression.